Don't Lead Alone: Think Like a System, Act Like a Network, Lead Like a Movement! - Justis, Cleveland; Student, Daniel (Fast Company Press, 2023)
Think. Act. Lead.It seems simple enough. But understanding your desire d impact and how it fits into a larger picture, connecting your work t o others and finding new collaborators, and bringing those collaborato rs together and moving them in a unified direction is never easy.Gover nments, businesses, and nonprofits all have unique approaches and idea s that many of us learn through our work. Yet, we rarely consider the skills needed to create and maintain the partnerships between them. Mo st of us learn those skills through trial, error, and often, failure. Worse, we typically stay in our self-reinforcing silos, sharing perspe ctives and frustrations with like-minded people, limiting our vision o f what our work can become. By partnering with other sectors, we combi ne and adapt approaches to solve complex problems, and leaders in any industry can create large-scale change.Cleveland Justis and Daniel Stu dent share a road map for effective partnerships that increase impact and profitability. Using real-life examples and practice exercises, th e authors teach how to acquire and use skills to solve complex problem s and propel your organization forward by combining a multitude of per spectives, split into three sections:Think Like a SystemAct Like a Net workLead Like a MovementIt’s time to get out of our silos. Don’t lead alone.